THE ISSUE OF CLASSIFICATION OF SPEECH SOUNDS IN UZBEK LINGUISTICS (Scientific journal of the Fergana State University, 2024)
Since the phonetic research in Uzbek linguistics was carried out under the influence of the researches of Russian linguists, in many analyzes there is a predominance of opinions related to the Russian language.It is known that the phonetics of the Uzbek language was originally created in collaboration with V. Reshetov and Sh. Shoabdurakhmanov. In this work, they provided information about speech sounds and phoneme relationships, sound changes, syllables and accents. After them, A.N. Kononov, in his work on the modern Uzbek literary language, focused on phonetics and was content with providing information in this area. Due to the fact that these linguists were Russian linguists, they applied some phonetic laws of the Russian language to the Uzbek language. This description of phonetics is typical of Uzbek linguists. This is especially evident when noting that word stress in Uzbek is dynamic in nature [1,55-78; 2,78-96; 3,165;]. It should be noted here that according to M. Mirtojiyev's point of view, word stress in Uzbek is quantitative. The description given in the Uzbek language textbooks issued for higher educational institutions does not differ from the above. Only H. Jamolkhanov notes that another branch of phonetics is intonation and its components [3,170-173]. But H. Jamolkhanov is limited to this.